Analisis Framing Pemberitaan PONPUS Al-Zaytun Pada Media TvOneNews.Com Dan CNN Indonesia - Nourma Goepita Laras; Candra Darmawan; Jufrizal Jufrizal (Social Science and Contemporary Issues Journal, 2024)
Currently, the pattern of education in Islamic boarding schools is known for instilling good values in them. Islamic boarding schools are traditional educational institutions in Indonesia which have an important role in the spiritual and intellectual development of students. In this research, researchers found confusing news regarding religious deviations that occurred at the Al-Zaytun Islamic boarding school. The Islamic boarding school is suspected of cultivating values that deviate from religious law. The case of religious deviation at the Al-Zaytun Islamic Boarding School has made many headlines and is in the public spotlight. The aim of this research is to find out how the reporting on cases of religious deviation at the Al-Zaytun cottage in West Java, Indramayu Regency is reported. In this research, researchers used qualitative research methods with a descriptive model. The descriptive model is intended to collect detailed actual information that describes existing symptoms, identify to collect detailed actual information that describes existing symptoms, identify problems, and make comparisons, identify problems or examine applicable conditions and practices, make comparisons or evaluation, and determining what other people did in facing the same problem and learning from their experiences to make plans and decisions in the future. Next, the theory used by researchers is the framing theory model of Zhongdang Pan and Gerald M. Kosicki. Basically, framing analysis is used to see how events are understood and framed by the media. There are four elements used in Pan and Gerald M. Kosicki's zhongdang model, namely, syntax, script, thematic, and rhetorical. Researchers found prominent differences in the packaging of news related to the issue of religious deviation indicated at the Al-Zaytun Islamic Boarding School on the media tvonenews.com and CNN Indonesia. KEYWORDS: framing and Islamic boarding school al-zaytun Copyright holder:© Nourma Goepita Ramadhita., jufrizal, Candra darmawan, (2024). Published by:ScidacplusJournal website:https://journal.scidacplus.com/index.php/sscij/ E-ISSN: This article is under: How to cite:Nourma Goepita Ramadhita., jufrizal, candra darmawan , (2024) analisis framing ponpes al-zaytun pada media tvonews dan cnn indonesia. Social Science and Contemporary Issues Journal, 1(2)